Ethnomodelling: Aboge Cikakak Calendar Convertion into Gregorian Calendar using Brute Force Algorithm - Agung Prabowo, Mustafa Mamat, Sukono, Pramono Sidi, and Wahyudin (International Journal of Advanced Science and Technology, 2020)
Cikakak Indigenous Village Community, Wangon Sub-District, Banyumas Regency, Central Java Province is known as the follower of Islam Aboge (Alif Rebo Wage). They use two types of encoding, namely year encoding and month encoding to determine the beginning of Ramadhan (fasting) and the beginning of Shawwal (Eid al-Fitr). However, in order to determine the Gregorian date, they need to look at the calendar. By using Brute Force algorithm, the beginning of fasting and Eid al-Fitr of the Aboge Calendar can be directly determined for the corresponding Gregorian dates.